Experimental characterization of a cyclist's wake - Adam, F.; Terra, W.; Sciacchitano, A. (Journal of Science and Cycling, 2019)
Large-scale particle image velocimetry (PIV) is used to characterize the dynamics of the unsteady wake of a non-pedalling full-scale cyclist. This to provide better understanding of the flow structures that generate the aerodynamic drag. Instantaneous flow fields are acquired and averaged to obtain the time-average flow topology. Afterwards, Proper Orthogonal Decomposition (POD) analysis is conducted using the instantaneous flow fields to identify the most energetic structures in the cyclists wake. The first mode is associated with a tilting of the main vortex pair emanating from the hip and thighs, while the second mode noticeably increases/decreases the strength of this vortex pair. This suggests that the main vortex pair rotates and shrinks/grows in time, which can be attributed to an unsteady separation location. From these results, it can be concluded that PIV has the potential to measure instantaneous velocity fields using aerodynamic investigation in cycling and allows an analysis of the instantaneous velocity fields by POD revealing the most energetic flow structures in the cyclist`s wake. Finally, application of the conservation of momentum enables the determination of the aerodynamic drag of the wind tunnel model. Although the absolute drag from the PIV wake rake is 5% off from the balance reading, the relative drag uncertainty is close to 1%.